2017
DOI: 10.1155/2017/3437169
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Diaphragm Lipid Content after Administration of Streptozotocin and High-Fat Diet Regime

Abstract: The diaphragm is a dome-shaped skeletal muscle indispensable for breathing. Its activity contributes up to 70% of the total ventilatory function at rest. In comparison to other skeletal muscles, it is distinguished by an oxidative phenotype and uninterrupted cyclic contraction pattern. Surprisingly, the research regarding diaphragm diabetic phenotype particularly in the light of lipid-induced insulin resistance is virtually nonexistent. Male Wistar rats were randomly allocated into 3 groups: control, streptozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…1. The predominant ceramide species in the diaphragm was C18, in agreement with previous reports (19,40). Two-way ANOVA showed no significant interaction effect for any ceramide subspecies or total ceramide.…”
Section: Pharmacological Interventionsupporting
confidence: 92%
“…1. The predominant ceramide species in the diaphragm was C18, in agreement with previous reports (19,40). Two-way ANOVA showed no significant interaction effect for any ceramide subspecies or total ceramide.…”
Section: Pharmacological Interventionsupporting
confidence: 92%
“…The results seem to be rather in line with the common belief that EL level is higher in tissues characterized by high O 2 consumption and rich vascularization, after all, EL is produced by endothelium lining blood vessels. The heart and diaphragm seem to fit nicely in this pattern since they are both tissues with high oxidative capacity, and uninterrupted rhythmical contractile patterns [ 38 , 39 ]. The right ventricle, however, resembles rather skeletal muscle in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with this, it has been shown that HFDs were able to increase circulating, as well as tissue ceramide levels, in animal models. Indeed, an increase in ceramides C16:0 and C22:0 [ 62 , 63 ] was reported in the liver, whereas an induction of ceramide C18:0 was detected in the skeletal muscle of high-fat-fed rodents [ [64] , [65] , [66] ].…”
Section: The Effect Of Nutrients On Circulating and Tissue Levels Of ...mentioning
confidence: 99%